Estrategias metodológicas para niños con trastorno de déficit de atención de 4 a 5 años de edad - Carrillo Yagchirema, Mirka Carolina (2022)
The general objective of this project is to determine the aspects presented by children with attention deficit disorder from four to five years old through the application of methodological instruments that focus on the 5 areas of development in order to suggest methodological strategies; based on the inductive methodology where the observation of the child's behavior, habits and daily school routines is prioritized. Information related to ADD and methodological strategies should be taken into account so that they can be proposed in the teaching-learning process, research techniques and instruments to identify the characteristics of children from 4 to 5 years old who have this need and the factors that influence the five areas of development. It is concluded that in order to carry out the present project, each of the bibliographic sources was objectively selected considering methodological strategies and essential techniques that can be developed both in children with ADD and with the rest of the class, for their academic development. It is also concluded that both the Ministry of Education and the educational units should promote a greater number of training campaigns for teachers and parents to deal with children with attention deficit disorder, in this way the progress of children in the school environment would be satisfactory. Finally, through the research process, it has been possible to prove that the aspects presented by children with ADD have an influence on the 5 developmental stages, so the suggestions of different techniques and methods according to the children's needs are taken into consideration. The project has a social impact that sporadically involves teachers and they take into account the importance of training and updating their knowledge about this need and the strategies they can implement.